Cross-culture adaptation and validation of the Indonesian version of the Hospital Survey on Patient Safety Culture (HSOPSC 2.0) - Lilis Suryani; Santhna Letchmi; Faridah Binti Moch Said (Belitung Nursing Journal, 2022)
Background: Hospital Survey on Patient Safety Culture (HSOPSC) is considered one of the most scientifically rigorous tools available with excellent psychometric properties. However, it is not yet available in an Indonesian version. Objective: This study aimed to determine the validity of the content and psychometric properties of HSOPSC 2.0 for use in Indonesian hospitals. Methods: The study was divided into three stages: translation, adaptation, and validation. Culture-adaptation was assessed using cognitive interviews with ten direct care nurses who worked in the hospital to evaluate their perceptions and the coherence of the translated items, response categories, and questionnaire directions. Content validity was also done by ten experts from academic and clinical settings. Finally, Confirmatory Factor Analysis (CFA) and reliability testing were conducted among 220 nurses from two Indonesian hospitals. Results: The cognitive test results indicated that the language clarity was 87.8 % and 84.5% for cultural relevance. The Content Validity Index (CVI) ranged between 0.73 to 1.00, while the construct validity results indicated that each factor had factor loadings above 0.4, from 0.47 to 0.65. The fit indices showed an acceptable fit for the data provided by the 10-factor model, with RMSEA = 0.052, SRMR = 0.089, and CFI = 0.87. The Pearson correlation coefficients between the ten subscales ranged from 0.276 to 0.579 (p < 0.05). The Cronbach’s alpha for all sub-scales was more than 0.70, except for organizational learning – continuous improvement, response to error, and communication openness. Conclusion: This study offers initial evidence of the psychometric properties of the Indonesian-HSOPSC 2.0. Future studies are needed to examine its psychometric features to improve generalizability. However, nurses and other healthcare professionals could use the tool to measure hospital patient safety culture in Indonesia.